Muslim American Youth : Understanding Hyphenated Identities through Multiple Methods. - Sirin, Selcuk R.; Fine, Michelle (Qualitative studies in psychology., 2008)
Since the terrorist attacks of September 11, 2001, and the subsequent "war on terror," growing up Muslim in the U.S. has become a far more challenging task for young people. They must contend with popular cultural representations of Muslim-men-as-terrorists and Muslim-women-as-oppressed, the suspicious gaze of peers, teachers, and strangers, and police, and the fierce embodiment of fears in their homes. With great attention to quantitative and qualitative detail, the authors provide heartbreaking and funny stories of discrimination and resistance, delivering hard to ignore statistical evidence.